Trends in Cyber Dispute Resolution Through Mediation - Gatot Efrianto; sabela Gayo (Faculty of Law, Universitas Pekalongan, 2025)
The development of Information Technology has encouraged the emergence of various disputes in cyberspace (cyber disputes), which have different characteristics from conventional disputes. Cyber disputes require an efficient, fast, and effective resolution mechanism. Mediation as an Alternative Dispute Resolution (ADR) method is a relevant solution because it is flexible, private, and efficient. This paper aims to examine the urgency of the use of mediation in cyber dispute resolution as well as the challenges and opportunities of its application in Indonesia. By using normative-juridical methods and conceptual approaches, this paper outlines the potential of online mediation (Online Dispute Resolution) supported by Information Technology in providing equal justice and easy access for the parties